2022
DOI: 10.3390/toxics10060310
|View full text |Cite
|
Sign up to set email alerts
|

Copper Monitoring in Vineyard Soils of Central Italy Subjected to Three Antifungal Treatments, and Effects of Sub-Lethal Copper Doses on the Earthworm Eisenia fetida

Abstract: The extensive employment of copper-based fungicides has increased copper concentration in vineyard soils. The present study’s objectives were to monitor copper concentration in two vineyard soils during two cropping seasons and study the ecotoxicological effects on the earthworm Eisenia fetida. Total, soluble, and bioavailable copper fractions were measured at the end of two cropping seasons and different depths in two vineyards of central Italy, characterised by three anticryptogamic control methods: copper c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
2
0
0
Order By: Relevance
“…Earthworm trophic activity decreased following high Cu exposure, as reported by other authors (Tatsi et al 2018 ). Similar biomass trends with a weight gain up to a critical Cu concentration followed by a significant weight loss at higher concentrations was also shown in other experiments (De Bernardi et al 2022b ; Clasen et al 2021 ; Owojori et al 2010 ); these occurrences are common in the presence of toxicants and are clearly associated to hormesis phenomena. In the earthworm reproduction test by Lukkari et al ( 2005 ) conducted on a high organic content substrate (~ 7%), the biomass of A. tuberculata was increased at intermediate Cu doses ranging from 53 to 79 mg/kg, while it decreased at the highest tested concentrations ranging from 119 to 268 mg/kg.…”
Section: Resultssupporting
confidence: 85%
“…Earthworm trophic activity decreased following high Cu exposure, as reported by other authors (Tatsi et al 2018 ). Similar biomass trends with a weight gain up to a critical Cu concentration followed by a significant weight loss at higher concentrations was also shown in other experiments (De Bernardi et al 2022b ; Clasen et al 2021 ; Owojori et al 2010 ); these occurrences are common in the presence of toxicants and are clearly associated to hormesis phenomena. In the earthworm reproduction test by Lukkari et al ( 2005 ) conducted on a high organic content substrate (~ 7%), the biomass of A. tuberculata was increased at intermediate Cu doses ranging from 53 to 79 mg/kg, while it decreased at the highest tested concentrations ranging from 119 to 268 mg/kg.…”
Section: Resultssupporting
confidence: 85%
“…The average contents of available copper in the examined soil samples were estimated to a value of 12.09 mg/kg in the organic and 7.90 mg/kg in the conventional farming. These are similar to the concentrations found in other monitoring campaigns of copper contents in vineyard soils (Miotto et al, 2014, De Bernardi et al, 2022. Other authors, , Ninkov et al (2014), Ambrosini et al (2018), andFernandez-Calvino et al (2008) identified significantly higher copper contents (> 20mg/kg) in their research of vineyard soils.…”
Section: Variantssupporting
confidence: 88%